Integration of Modern Psychological Coping Theory and the Concepts of Tawaduk-Izzah: Educators’ Coping Strategies in Facing Workplace Relationship Dynamics within Islamic Educational Environments - Atho, Ibnu; Fahrezi, Fatur; Musonif, Irfan (SENTRI: Jurnal Riset Ilmiah, 2025)
Teachers in Islamic educational environments face complex psychological pressures arising from workplace relationship dynamics, professional demands, and social expectations. Although previous studies have examined teacher stress, burnout, and coping strategies, limited research has explored how Islamic moral values function as psychological resources in educators’ coping processes. This study aims to examine educators’ coping strategies by integrating modern psychological coping theory with the Islamic values of tawaduk (humility) and izzah (dignity and self-respect). This study employed an interpretive qualitative approach with a field-based conceptual design. Data were analyzed using reflexive thematic analysis to identify patterns of workplace pressure, psychological responses, coping strategies, and the role of Islamic values in adaptation processes. The findings indicate that workplace relationship pressures are mediated by cognitive appraisal and managed through problem-focused coping, emotion-focused coping, and meaning-focused coping. Furthermore, tawaduk and izzah function as complementary psychological resources: tawaduk supports humility, emotional regulation, and ethical conduct, while izzah strengthens professional dignity, boundaries, and respectful assertiveness. This study proposes an integrative coping model showing that educators’ resilience is developed through the interaction between psychological mechanisms and Islamic moral values. The findings contribute to Islamic psychology and provide practical implications for strengthening educators’ mental health and sustainable professionalism